DPR DAN REFORMASI POLRI Kajian Evaluatif Fungsi DPR terhadap Pelaksanaan Reformasi Polri - Siregar, Sarah Nuraini (Jurnal Penelitian Politik, 2011)
The implementation ofPolri Reform and its accountabilityprincipal is determined by manyfactors One ofthefactors is the parliament roles andfunctions It is showed us thatparliament has an important role in guarding theimplementation ofPolri Reform through the parliamentfunctions which are legislation function budgetfunctionand supervisionfunction This article is to analyze the implementation ofparliamentfunction which related to PolriReformation Are parliamentfunctions be effective as a key tools for Polri Reformation or precisely has not beeneffective And how does the impact ofparliamentfunction to the implementation ofPolri Reform